The journal of James Macrae botanist at the Sandwich Islands, 1825 - Macrae, James (North Beach-West Maui Benefit Fund Inc., 2019)
This volume is a transcription of the original manuscript journal kept by Scottish botanist James Macrae when he traveled with Lord Byron on HMS Blonde during its 1824-1825 voyage from England to the Hawaiian Islands. A primary purpose of the expedition was to return the bodies of King Kamehameha II (Liholiho) and Queen Kamāmalu, both of whom had died of measles during a diplomatic visit to Britain. Macrae also brought plants to Hawai'i and made observations wherever he sailed. After almost three months in the islands, the ship returned to Britain and Macrae's journal was given to the Royal Horticultural Society. Extracts were published in 1922, but a complete transcription of the journal from the time Macrae spent in Hawai'i has not previously been available.